2012
DOI: 10.1002/anie.201107724
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin—From Molecule to Biological Function

Abstract: Turmeric is traditionally used as a spice and coloring in foods. It is an important ingredient in curry and gives curry powder its characteristic yellow color. As a consequence of its intense yellow color, turmeric, or curcumin (food additive E100), is used as a food coloring (e.g. mustard). Turmeric contains the curcuminoids curcumin, demethoxycurcumin, and bisdemethoxycurcumin. Recently, the health properties (neuroprotection, chemo-, and cancer prevention) of curcuminoids have gained increasing attention. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
576
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 782 publications
(591 citation statements)
references
References 244 publications
(313 reference statements)
7
576
0
8
Order By: Relevance
“…The content of turmeric curcuminoids may vary between 2 and 9%, depending on geographic conditions (Esatbeyoglu et al, 2012). In general, starch is the component present in greater proportion, as observed in this study by scanning electron microscopy.…”
Section: Resultssupporting
confidence: 59%
“…The content of turmeric curcuminoids may vary between 2 and 9%, depending on geographic conditions (Esatbeyoglu et al, 2012). In general, starch is the component present in greater proportion, as observed in this study by scanning electron microscopy.…”
Section: Resultssupporting
confidence: 59%
“…Curcumin, or turmeric, which is derived from the root of the plant Curcuma longa Linn, has been used as a treatment for inflammatory conditions in Ayurvedic medicine for centuries [8] . It has been reported that curcumin attenuates neurobiological deficits in animal models of different neurological disorders, including Parkinson's disease [9] , brain trauma [10] , ischemic stroke [11] , and subarachnoid hemorrhage (SAH) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, its medical benefits are restricted by low aqueous solubility, poor intestinal absorption, and chemical instability in the physiological environment, resulting in low bioavailability. 4) Many approaches have been developed to overcome these intrinsic barriers to bioavailability, including co-administration of CUR with inhibitors of glucuronidation, nano-formulations with lipids and polymers, amorphous solid dispersions, and prodrugs by conjugation.…”
Section: Curcuminmentioning
confidence: 99%